Integration of Altimeter and GPS Sensors on IoT-Based Drone Delivery System (DDS) - Tay, Fei Siang; Yan Chieng Jake, Zen; Then, Yi Lung (IET Digital Library, 2023)
As the trend of online shopping increased, the demand for cheaper and quicker delivery became apparent. Hence, the proposed IoT-based DDS is targeted as an alternative to decreasing the price and time taken to perform the delivery operation. This system will extract the current altitude and position of the drone via the MPL3115A2 altimeter sensor and GY-NEO6MV2 GPS module attached to the drone. The ESP32 NodeMCU would collect sensor measurement and transmit this information to the cloud server hosted on AWS EC2 virtual machine wirelessly via Wi-Fi. The recipient and operator can access the dashboard through the cloud server to perform operations such as tracking, registering, confirming, and dropping parcels. The servo motor attached to the drone would automatically facilitate parcel dropping through a simple release mechanism.